2005
DOI: 10.2106/jbjs.d.02826
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy in the Measurement of Compartment Pressures: A Comparison of Three Commonly Used Devices

Abstract: Side-port needles and slit catheters are more accurate than straight needles are. The arterial line manometer is the most accurate device. The Stryker device is also very accurate. The Whitesides manometer apparatus lacks the precision needed for clinical use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(81 citation statements)
references
References 15 publications
1
77
0
3
Order By: Relevance
“…9 The resulting pressures in the right and left erector spinae muscles were 108 and 21 mm Hg, respectively. The CK at this time was 72,820 U/L, and the other peak laboratory values are presented in Table 1.…”
Section: Case Reportmentioning
confidence: 95%
“…9 The resulting pressures in the right and left erector spinae muscles were 108 and 21 mm Hg, respectively. The CK at this time was 72,820 U/L, and the other peak laboratory values are presented in Table 1.…”
Section: Case Reportmentioning
confidence: 95%
“…Degree of severity reporting introduces intraobserver/interobserver variability and further confounds the data. Finally, difference in mean interstitial fluid pressure, as measured by a side port needle or slit catheter [3], could influence the soft tissue swelling generated by intraarticular hydrostatic forces. This also may be true regarding shaver time and the type of blade used.…”
Section: Discussionmentioning
confidence: 99%
“…In our case, we did not measure the pressure since the diagnosis was clear. Boody and Wongworawat [17] in an experimental study have compared three commonly used devices and concluded that side-port needles and slit catheters were more accurate than straight needles. The arterial line manometer was the most accurate device, the Stryker device was also very accurate and the Whitesides manometer apparatus lacks the precision needed for clinical use in their study [17].…”
Section: Discussionmentioning
confidence: 99%